The Semantics and Pragmatics Analysis of Javanese and English Apologetic Speech Acts - Betari Irma Ghasani (Faculty of Economics, Law, and Humanities, 2018)
Reconsidering the role of apologizing as one of fundamental aspects in speech act learner has become important nowadays. It is argued that acquiring apologizing speech act can build their attitude. The purpose of this study is analyzing semantic and pragmatic of Javanese apologetic speech act, especially with respect how Javanese apologetic speech act expression differ conceptuallyfrom English expression. In order to fi nd out the differences between Javanese apologetic speech act nuwun sewu”and English speech act sorry, I used the natural semantic metalanguage proposed by Wierzbicka (1987). Furthermore, I described some distinguishable features of Javanese culture as well. By using Blum-Kulka (1989) and her collaboration model, I analyzed Javanese apologyspeech act strategies found in several conversations and situations. The fi ndings of my study are the attitudinal meanings of nuwun sewu and sorry, as well as the illocutionary acts associated with the two expressions are different. My study further suggests that conceptualizing speech act expressions, using semantically simple words, may help second learners acquire the proper ways of using speechacts in the target language and culture.